2015
DOI: 10.5294/aqui.2015.15.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Lo que no se ve, no existe: percepciones sobre cáncer y papilomavirus humano en jóvenes universitarios, Medellín, Colombia, 2014

Abstract: Para citar este artículo / To reference this article / Para citar este artigo Tamayo-Acevedo LS, Gil-Cano PA, Tamayo-Acevedo, LE. Lo que no se ve, no existe: percepciones sobre cáncer y papilomavirus humano en jóvenes universitarios, Medellín, Colombia, 2014. Aquichan. 201515(2):253-270. DOI: 10.5294/aqui.2015.15.2.9 resumeN Objetivo: comprender las percepciones de los estudiantes de pregrado de la Universidad de Antioquia, Colombia, sobre los cánceres de cuello uterino, canal anal, orofaringe y pene, y có… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
1
0
3
Order By: Relevance
“…Knowledge also accounts for the tools that young people have to protect themselves against infection, and this is one of the most studied aspects in research on HPV; Risk behaviors and, therefore, the preventive part are identified, but they are unaware of its associa-tion with cervical cancer and whether or not there are symptoms, which is why it is often confused with other STIs such as herpes, gonorrhea or HIV/AIDS. However, in addition to sexual behavior and knowledge, an aspect little studied was identified within risk; perception: it is recognized that the risk is greater among women since the man is a carrier (23), but in this study, it is men who are recognized as more susceptible to becoming infected, which was revealing and interesting data from analyze; and this can be related to how they provide care, an aspect that will be discussed later.Finally, how young adults take care of themselves starts from the transmission factors themselves. Still, with some particularities: of the three known risk behaviors, the one most related to HPV is that of multiple sexual partners; the use of condoms is referred to as a preventive method, being this more common and accessible, although more towards avoiding pregnancies (24) and, the age of onset is not considered as a conduit of transmission, neither risky nor much less preventive.…”
Section: Carefulmentioning
confidence: 84%
“…Knowledge also accounts for the tools that young people have to protect themselves against infection, and this is one of the most studied aspects in research on HPV; Risk behaviors and, therefore, the preventive part are identified, but they are unaware of its associa-tion with cervical cancer and whether or not there are symptoms, which is why it is often confused with other STIs such as herpes, gonorrhea or HIV/AIDS. However, in addition to sexual behavior and knowledge, an aspect little studied was identified within risk; perception: it is recognized that the risk is greater among women since the man is a carrier (23), but in this study, it is men who are recognized as more susceptible to becoming infected, which was revealing and interesting data from analyze; and this can be related to how they provide care, an aspect that will be discussed later.Finally, how young adults take care of themselves starts from the transmission factors themselves. Still, with some particularities: of the three known risk behaviors, the one most related to HPV is that of multiple sexual partners; the use of condoms is referred to as a preventive method, being this more common and accessible, although more towards avoiding pregnancies (24) and, the age of onset is not considered as a conduit of transmission, neither risky nor much less preventive.…”
Section: Carefulmentioning
confidence: 84%
“…También se han realizado estudios sobre la percepción de padres de familia de adolescentes respecto a la aplicación de la vacunación en niñas antes del inicio de la vida sexual. Resaltan que padres y madres de colegios privados mostraron mayor aceptabilidad de la vacuna; mientras que las/os de colegios públicos tuvieron reservas a la aplicación de dicha biotecnología, pues consideran que podría incentivar la "promiscuidad" en sus hijas (88)(89)(90)(91). Más aún, un debate en los medios de comunicación ha culpado a la vacuna de muertes, enfermedades e incluso parálisis, hasta de 800 adolescentes, después de haber recibido la vacuna.…”
Section: El Caso De La Vacuna Preventiva Del Vphunclassified
“…Tais percepções poderiam, segundo os autores, fornecer subsídios no desenvolvimento de estratégias preventivas e abordagens diferenciadas nos programas de educação sexual e sexualidade, bem como contribuir na qualificação dos profissionais a fim de proporcionar cuidado integral a esse contingente de pessoas 20 .…”
Section: Issn 2317-2460unclassified